A SYSTEM FOR CUSTOMER CHURN PREDICTION USING WEB LOG FILES - Aditya Narayan; Vikas Nandgaonkar; Soumitra Das; Sunil Rathod (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The World Wide Web is a significant part of the Internet which is the biggest publishing system in the world. Web analytics is increasing at a very rapid rate ever since the growth of the World Wide Web. Web analytics is the tool for the collecting, measuring, analyzing and reporting of web data and information to understand and optimize web usage. The paper focuses on the implementation of a system that helps to track record and analyze the users as soon as users enter and leaves the system. The users time spent on a particular web page is recorded, from which the statistics is generated which helps the system to analyze the users traffic in the website along with total number of hits, total new visitors, percentage of new users, date of access. Such type of analysis helps to find out the cause that deviate the customer from the web site, so that improvement can be carried out to attract the attention of the new visitors to the website.